Perception of the general population on Epilepsy and Antiepileptic drugs: A questionnaire-based study - Vijayamathy Arunnair; S Bhuvaneshwari; M S Umamageswari; A T Sathiya Vinotha; S Jeevithan; Samuktha Venkatesan (Krupanidhi College of Pharmacy, 2023)
The impact of epilepsy is multidimensional, ranging from socioeconomic to medical to psychological problems. The additional burden on quality of life is not only due to disease but also to the antiepileptic medication-related adverse effects. Though the majority of epileptics dwell in developing countries, studies have found a lack of knowledge, attitude, and practice towards epilepsy and its management, leading to a large treatment gap. This study aimed to assess the knowledge, attitude, and practice of epilepsy and antiepileptic medication among the general population, including epileptics or caregivers. A 6 month (August 2022 to February 2023) prospective, cross-sectional online questionnaire-based study utilizing Google Forms as a data collection tool was conducted among the general population at a tertiary care hospital in Coimbatore employing convenient sampling. Descriptive and inferential statistics (paired t-test, chi-square test) were used. The results were presented as numbers and percentages. The data obtained was analyzed using Statistical Package for the Social Sciences, version 27. We received 123 responses. 87.8% and 85.4% linked epilepsy to insanity and spiritual possession/trance, respectively. More than 90% opined that epilepsy was contagious, due to patient or ancestral sins, and treatable by faith healers. The mean knowledge, attitude, and practice scores (%) were found to be 78.04 ± 1.32, 71.23 ± 1.23, and 53.15 ± 1.38, respectively. Even though the urban population had satisfactory knowledge, the same was not translated into attitude and practice. There was a wide gap between knowledge, attitude, and practice. Considering the significant disparities in awareness, attitude, and practice even after decades in urban regions, policymakers and public health professionals must incorporate health education programs and healthcare services for the masses to bring about changes in a country like India. Keywords Knowledge, Attitude, Practice, Stigma, Quality of life, People living with epilepsy